Ultradeformable phospholipid vesicles as a drug delivery system: a review - Romero, Eder Lilia (2015)
Ultradeformable vesicles are highly deformable (elastic/flexible) liposomes made of phospholipids plus highly mobile hydrophilic detergents capable of penetrating the intact skin across the stratum corneum and reach the viable epidermis. Ultradeformable vesicles are more effective than conventional liposomes in delivering drugs into and across the mammalian skin, and have been tested for local delivery of non-steroidal anti-inflammatory agents against musculoskeletal-articular disorders such as osteoarthritis, to treat atopic dermatitis, to deliver anti-infective drugs against epithelial infections and to avoid the first pass effect of oral antihypertensive drugs. Currently a single ultradeformable vesicle anti-inflammatory formulation has reached phase III clinical trials, but no commercial product based on this technology is yet available.